2007
DOI: 10.2527/jas.2006-343
|View full text |Cite
|
Sign up to set email alerts
|

Deposition rates and accretion patterns of intramuscular fat, loin muscle area, and backfat of Duroc pigs sired by boars from two time periods1

Abstract: A study was conducted to evaluate differences in performance and in carcass composition and tissue deposition rates between purebred Duroc pigs sired by boars currently available and those sired by boars from the mid-1980s. Two lines were developed by randomly allocating littermate and half-sib pairs of females to matings by current time period (CTP) or old time period (OTP) boars. Pigs from 2 replications were placed on test at a group mean BW of 63.5 kg. Serial ultrasonic measurements of the 10th-rib LM area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Animal growth performance has recently been improved by genetic selection, comfortable circumstances, and optimal nutrition, though these advances have been at the cost of meat quality [1]. IMF is one of the most important indexes of meat quality, and is positively correlated with factors such as shearing force, tenderness, and flavor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal growth performance has recently been improved by genetic selection, comfortable circumstances, and optimal nutrition, though these advances have been at the cost of meat quality [1]. IMF is one of the most important indexes of meat quality, and is positively correlated with factors such as shearing force, tenderness, and flavor.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, the growth performance of domestic animals has been improved by genetic selection, comfortable circumstances, and optimal nutrition, which has led to poor meat quality [1]. Intramuscular fat (IMF) is one of the main factors affecting meat quality, and has attracted increasing attention in animal production [2,3].…”
mentioning
confidence: 99%
“…107 Long-term selection for decreased backfat in pigs was highly associated with decreased IM as well. 108 Selection for lean growth in sheep also significantly reduced IM. 109 A study of cattle selected for high growth indicated no change in IM lipid despite a significant increase in backfat accretion.…”
Section: Adipocyte Development Within Immentioning
confidence: 97%
“…The Shanzhu pigs, one of the indigenous pigs in Jiangsu Province of China, are fatty pigs characterized by their good meat quality and a high level of IMF content. By contrast, the Duroc pig is an international breed mainly concentrated on the lean growth efficiency (Schwab et al 2007). Therefore, Shanzhu × Duroc crossbred pigs might possess good meat and fatness traits determined by IMF content and fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%